Marketing Adaptation in Sharia Based Cooperative Finance during a Global Health Crisis - Ma'ruf, Aminudin; Ahmad Athoillah Azzakiy; Sausan Liski Aulia; Shahbaz Alam (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Purpose: This study aims to examine how Sharia based cooperatives adapted their marketing strategies for financing products during the COVID 19 pandemic, with a focus on Sharia cooperatives operating in Klaten City. The study also explores the key obstacles faced and the solutions adopted during the global health crisis. Method: This research employs a qualitative field research approach using inductive analysis. Data were collected through in depth interviews with managers of four Sharia cooperatives or Baitul Maal wat Tamwil institutions in Klaten City to capture institutional responses to pandemic related disruptions. Result: The findings show that Sharia cooperatives adapted their marketing strategies by targeting business sectors that remained active, applying the marketing mix strategy covering product price place and promotion, and strengthening marketing communication with members. However, several challenges emerged, including social distancing restrictions, intense institutional competition, and limited human resource capacity in Sharia financing and digital marketing. Implication: The study highlights the importance of adaptive marketing strategies and digital readiness to ensure the sustainability of Sharia cooperative finance during crisis conditions. Originality: This study provides empirical insights into marketing adaptation strategies of Sharia cooperatives during a global health crisis, contributing to the literature on Islamic cooperative finance and crisis management.